EFEKTIVITAS TERAPI HERBAL QING FEI PAI DU TANG TERHADAP NYERI SENDI DENGAN DIAGNOSIS SINDROM LEMBAB-DINGIN (HAN SHI ZHENG) DI PUSAT TERAPI BSM JAKARTA - Hilman Rama Pratama; Hari Iskandar Kang; Stefanus Aditya; La Ode Muhammad Anwar (Journal of Innovation Research and Knowledge, 2025)
Hilman Rama Pratama / 224110019 / 2025 / The Effectiveness of Qing Fei Pai Du Tang Herbal Therapy on Joint Pain with a Diagnosis of Cold-Damp Syndrome (Han Shi Zheng) at the BSM Therapy Center Jakarta / Dr. Hari Iskandar Kang, B.C.M., M.C.M. Joint pain that arises after COVID-19 infection is a common manifestation of post- COVID conditions, often referred to as Long COVID. In Traditional Chinese Medicine (TCM), this condition is classified as Han Shi Zheng (cold-damp syndrome), characterized by joint stiffness, severe pain, and worsening symptoms in cold or humid environments. Qing Fei Pai Du Tang (QFPDT) is a classical herbal formula traditionally used to expel cold-damp pathogens, promote the circulation of Qi and Xue (blood), and warm the meridians. This study aimed to evaluate the effectiveness of QFPDT in reducing joint pain among patients diagnosed with Han Shi Zheng. A quasi-experimental one-group pre–post test design was applied, involving 30 patients at the BSM Therapy Center in Jakarta. Participants received QFPDT at a dosage of 6 grams per day for seven consecutive days. Evaluations were conducted using the Visual Analogue Scale (VAS) for pain, structured interviews, and tongue observations before and after therapy. The results showed an average reduction of 3.1 points in VAS scores, with 80% of participants experiencing significant pain relief. Tongue color changes from pale or purple to pink indicated improved Qi circulation and a reduction in pathological dampness. No serious adverse effects were reported. These findings demonstrate that QFPDT is clinically effective as a supportive therapy for alleviating joint pain in patients with Han Shi Zheng.